2020
DOI: 10.4269/ajtmh.19-0521
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Infection in Children in Fortaleza, Brazil: A 3-Year School-Based Prospective Cohort Study

Abstract: Dengue is endemic in Brazil. The dengue surveillance system's reliance on passive reporting may underestimate disease incidence and cannot detect asymptomatic/pauci-symptomatic cases. In this 3-year prospective cohort study (NCT01391819) in 5-to 13-year-old children from nine schools in Fortaleza (N = 2,117), we assessed dengue virus (DENV) infection seroprevalence by IgG indirect ELISA at yearly visits and disease incidence through active and enhanced passive surveillance. Real-time quantitative polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Wunderlich and cols [10] studied hospitalized patients with dengue in Brazil from 1998 to 2015 and demonstrated that until 2005, children between 0 and 9 years of age represented only 7% of dengue hospitalizations but this proportion increased rapidly in the following years with the largest yearly average occurring in 2008 (22%). A prospective 3-year study [11] of 5-13 years old school children in Fortaleza, the fifth most populous state capital in Brazil, demonstrated that at enrollment, 54.1% of children were DENV IgG-positive; during the course of the study, 32.8% of dengue-naive children experienced a primary infection.…”
Section: Key Pointsmentioning
confidence: 99%
“…Wunderlich and cols [10] studied hospitalized patients with dengue in Brazil from 1998 to 2015 and demonstrated that until 2005, children between 0 and 9 years of age represented only 7% of dengue hospitalizations but this proportion increased rapidly in the following years with the largest yearly average occurring in 2008 (22%). A prospective 3-year study [11] of 5-13 years old school children in Fortaleza, the fifth most populous state capital in Brazil, demonstrated that at enrollment, 54.1% of children were DENV IgG-positive; during the course of the study, 32.8% of dengue-naive children experienced a primary infection.…”
Section: Key Pointsmentioning
confidence: 99%
“… 23 Oct 2015–Mar 2016 A 0.030 (0.013, 0.055) anti-dengue IgG elisa kit (Abcam, Cambridge, UK) Brazil Fortaleza 05–13 9 2117 IgG capture ELISA CBC et al. 24 Sep 2011–Jan 2015 C 0.096 (0.080, 0.115) IgG capture ELISA (Panbio, Brisbane, Australia) Brazil Fortaleza 02–12 2 483 indirect IgG ELISA Zhang et al. 25 Nov 2019–Feb 2020 A 0.086 (0.024, 0.215) Panbio Dengue IgG nidirect ELISA Brazil Recife 05–65 6 2070 IgG for NS1 ELISA Braga et al.…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective study with active surveillance for fever among 3000 children 9-16 years of age, the incidence of laboratory-confirmed dengue per 1000 PY ranged from 0.4 in Natal to 9.0 in Campo Grande during 2010, and from 1.1 in Goiania to 6.6 in Fortaleza during 2011 (Dayan et al, 2015). A further prospective, school-based study with active and enhanced passive surveillance for dengue among children 5-13 years of age in Fortaleza identified the incidence of laboratory-confirmed dengue as 11.0, 18.1 and 10.2 per 1000 PY in 2012, 2013 and 2014, respectively (Coelho et al, 2020). Data on the incidence of dengue in adults in Latin America as a whole are also rare, but several studies report data in children.…”
Section: Discussionmentioning
confidence: 99%